Heterotopic Ossification: An Unusual Presentation - Satish G. Patil; Aaisha Siddiqua; Udupi Krishna Joshi; Pallavi K. Deshmukh; Bindu S. Patil; Anand Mangalgi (Case Reports in Dentistry)
Heterotopic ossification (HO) is usually seen after-trauma, following traumatic injuries, surgeries involving major joints, neurogenic injury, and burns; however, atraumatic cases have also been reported. HO tends to cause pain, swelling, and limitation of joint movements. HO has been reported in adults as well as in pediatric cases, however, our search in the English literature has not revealed a single case in the infratemporal region, especially in children of developing age, where HO tends to affect the development and growth of adjacent bones. We are reporting a case of HO in close proximity to TMJ affecting the development of mandible and maxilla.